Estudo termodinâmico dos processos avançados de oxidação utilizando a teoria do funcional da densidade: avaliação de possíveis reações de abstração de átomos de hidrogênio do Tenofovir pelo radical hidroxila - Daniel Furst Pessoa (2021)
Advanced Oxidation Processes, which are characterized by the generation of highly oxidizing species, such as the •OH radical, are gaining more and more prominence in scientific research. This is due, in particular, to the possibility of application in the treatment of effluents. The contaminants present in the aqueous medium can be various, such as textile dyes and food industry, hospitals, from the pharmaceutical industry or even inorganic compounds such as heavy metals. Among these contaminants, antiretrovirals fall into the category of emerging pollutants, which increases the need for studies on these compounds. An interesting approach to analyze the behavior in aqueous solution of some compounds involved in the POA's, such as the •OH radical itself or some contaminant, is through theoretical research. Thus, the proposed work was to carry out a theoretical study to investigate thermodynamic properties, such as Gibbs entropy and free energy, of the species involved in these processes. The •OH radical was one of the species studied, as well as the Tenofovir molecule, as an example of an antiretroviral. The studies initially involved the species in the gaseous state and later in the presence of water as a solvent. For that, the GAMESS software was used to calculate these properties. The substances in the gaseous state and in the presence of the solvent had their properties obtained through DFT calculations, using the hybrid functional B3LYP. The base function chosen for Tenofovir was 6-31G (d, p), while for the other species the base 6-311G (d, p) was used. Additionally, to investigate the influence of the solvent and calculate the solvation energies of the compounds, the PCM and EFP models were used. A thermodynamic study of the reaction between tenofovir and the •OH radical was also carried out using the DFT approach, at the B3LYP / 6-31G level. The calculations performed showed the thermodynamic properties of some species involved in the process, in addition to being able to predict the solvation of both •OH, OH-H2O aggregate and Tenofovir. They were also able to evaluate the variation of Gibbs energy involved in the abstraction of hydrogen atoms from Tenofovir by the radical •OH in aqueous medium.